Postmortem Microbiological Analysis a New Approach - Ziyade, Nihan (The Bulletin of Legal Medicine, 2014)
In the last century with discussions on the contribution of postmortem examinations to the diagnoses of autopsy cases and especially with the increase in using microorganisms as biological weapon, "forensic microbiology" and accordingly "postmortem microbiology" have appeared as fields that need to be worked upon and that requires training of experienced experts. Postmortem microbiological analyzes are useful in diagnosing the suspicious infection in clinical and judicial autopsies. Postmortem microbiological examination should be done both in order to detect the responsible factor and as a part of the judicial investigation in the cases of especially sudden death of infant and child and deaths that carry suspicion of infection. The role that infections play as a cause of sudden, unexpected deaths carries significance in terms of public health and epidemiology. Creating standard protocols for postmortem microbiological sampling would increase the quality of judicial autopsies as well as the possibility of detecting the cause of death. The multidisciplinary studies where microbiologists, pathologists and forensic medicine experts take part would both increase the success of postmortem microbiology and contribute to preventing epidemics and to creating a healthy population. Besides, sharing experience in the fields of science of epidemiology, microbiology and forensic science and organizing study groups are essential in our country. In this compilation, the aim is to discuss postmortem microbiology and its significance in the light of current information. Keywords: Postmortem Microbiology, Forensic Microbiology, Autopsy, Sudden Death